2005
DOI: 10.1002/jbt.20045
|View full text |Cite
|
Sign up to set email alerts
|

Quantitative structure-activity relationships for the pre-steady state acetylcholinesterase inhibition by carbamates

Abstract: 4-Nitrophenyl-N-substituted carbamates (1) are characterized as pseudosubstrate inhibitors of acetylcholinesterase. The first step is formation of the enzyme-inhibitor tetrahedral intermediate with the inhibition constant (Ki), the second step is formation of the carbamyl enzyme with the carbamylation constant (kc), and the third step is hydrolysis of the carbamyl enzyme with decarbamylation constant (kd). According to pre-steady state kinetics the Ki step is divided further into two steps: (1) formation of th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
16
0

Year Published

2005
2005
2010
2010

Publication Types

Select...
7

Relationship

5
2

Authors

Journals

citations
Cited by 15 publications
(17 citation statements)
references
References 33 publications
1
16
0
Order By: Relevance
“…The fractions of unionised species calculated from pK a data are important descriptors used in the TPAM model when describing partial transcelluar and paracelluar permeability models. In addition, it has been used for estimating the acidity or basicity of a compound's functional groups that might affect active binding sites [3,30]. McFarland et al used pK a and logP to generate QSAR mode to predict potencies of 15 known macrolides of diverse structures and found that these physicochemical properties are major determinants of macrolide antibacterial in vitro and in vivo potencies [31].…”
Section: A Relevant Descriptor In Qsar Modelsmentioning
confidence: 99%
“…The fractions of unionised species calculated from pK a data are important descriptors used in the TPAM model when describing partial transcelluar and paracelluar permeability models. In addition, it has been used for estimating the acidity or basicity of a compound's functional groups that might affect active binding sites [3,30]. McFarland et al used pK a and logP to generate QSAR mode to predict potencies of 15 known macrolides of diverse structures and found that these physicochemical properties are major determinants of macrolide antibacterial in vitro and in vivo potencies [31].…”
Section: A Relevant Descriptor In Qsar Modelsmentioning
confidence: 99%
“…Among such inhibitors are various alkyl-and aryl-carbamates and ureas responsible for the mechanism-based inhibition of enzymes by formation of carbamyl enzymes. Among these enzymes are fatty acid amide hydrolase (34,42), monoacylglycerol lipase (25), acetyl cholinesterase (21), and Pseudomonas species lipase (22). In all of these cases the enzyme forms a covalent carbamyl enzyme via the active-site serine, including in some cases via a substituted piperidine carbamyl link (25) as is the case with NXL104.…”
Section: Vol 54 2010 Inactivation Of ␤-Lactamases By Nxl104 5135mentioning
confidence: 99%
“…(7) ( Figure 6 and Table 2). The δ value of 0.08 for pK i -E s -π correlation indicates that the inhibitors 1-8 with less bulky ester moieties are easier to pass by the trumpet mouth of the enzyme (Figure 7) [7,37,[40][41][42][43].…”
Section: Discussionmentioning
confidence: 98%
“…The first step is protonation of inhibitor due to the basicity for the inhibitors [19,21,40]. The second step (K i ) is the formation of the enzyme-inhibitor tetrahedral intermediate.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation